Developing guidelines for the management of brain tumour related epilepsy. (15th October 2021) - Vacher, Elizabeth; Ruiz, Miguel Rodriguez; Rees, Jeremy
Abstract: Aims: Brain Tumour Related Epilepsy (BTRE) has a significant impact on Quality of Life with implications for driving, employment and social and domestic activities. Management of BTRE is complex due to the higher incidence of pharmacoresistance and the potential for interaction between anti-cancer therapy and anti-epileptic drugs (AEDs). Neurologists, oncologists, palliative care physicians and clinical nurse specialists treating these patients would benefit from up-to-date clinical guidelines. We aim to review the current evidence to adapt current NICE guidelines for Epilepsy and to outline specific recommendations for the optimal treatment of BTRE, encompassing both primary and metastatic brain tumours. Method: A comprehensive search of the literature from the past 20 years on BTRE was carried out in three databases: Embase, Medline and EMCARE. A broad search strategy was used and the evidence was evaluated and graded based on the Oxford Centre for Evidence-Based Medicine Levels of Evidence. Results: All patients with BTRE should be treated with AEDs. There is no proven benefit for the use of prophylactic AEDs, although there are no randomised trials testing newer agents. Seizure frequency varies between 10-40% (Class 2a evidence) in patients with Brain Metastases (BM) and from 30% (high-grade gliomas) to 90% (low-grade gliomas) (Class 2a evidence) in patients with Primary Brain Tumours (PBT). In patients with BM, risk factors include number of BM and melanoma histology (Class 2b evidence). In patients with PBT, risk factors include frontal and temporal location, oligodendroglial histology, IDH mutation and cortical infiltration (Class 2b evidence). There is a low incidence of seizures (13%) after stereotactic radiosurgery for BM (Class 2b evidence). Non-enzyme inducing AEDs are recommended as first line treatment for BTRE, but up to 50% of patients with BTRE due to PBT remain resistant (Class 2b evidence). Conclusion: The review has highlighted the relative dearth of high quality evidence for the management of BTRE, and provides a framework for further studies aiming to improve seizure control, quality of life, and indications for AEDs.